HUBUNGAN BEBAN KERJA DAN KELELAHAN KERJA DENGAN TURNOVER INTENTION PADA PEKERJA OUTSOURCING PT X TAHUN 2020 - Tillama, Putu Intan; Wirawan, I Made Ady (ARCHIVE OF COMMUNITY HEALTH, 2021)
ABSTRACT Occupation in airports are dominated by service provider sectors, such as ground handling which requires the workers to deal with the consumers directly, and are faced with high work intensity due to the tight flight schedules. Thus, it can affect the workload that received and prone to fatigue, and can cause turnover intention among workers. The turnover rate of outsourced workers at PT X in 2019 is 28%, with 197 people in total. If the annual turnover rate in a company reaches 10%, then the turnover in that company can be categorized as high. The aim of this study is to determine the correlation between workload and work fatigue with turnover intention in outsourced workers at airports. This analytical research with a quantitative approach using a cross-sectional design. The number of respondents are 137 people who were selected using the stratified random sampling method. Physical workload (p = 0.2702) and mental workload (p = 0.5181) have no correlation with turnover intention. Meanwhile, work fatigue has a positive mild correlation with turnover intention (p = 0.0056).   Keywords : ground handling, workload, work fatigue, turnover intention, outsourced workers